Comparison of Cortical Auditory Evoked Potential Findings in Presbycusis with Low and High Word Recognition Score - Gürkan, Selhan; Durankaya, Serpil Mungan; Mutlu, Başak; İşler, Yalçın; Uzun, Yiğit Ö.; Başokçu, Oğuz; Erdağ, Taner Kemal; Kırkım, Günay (Journal of the American Academy of Audiology, 2020)
Background Deteriorated speech understanding is a common complaint in elderly people, and behavioral tests are used for routine clinical assessment of this problem. Cortical auditory evoked potentials (CAEPs) are frequently used for assessing speech detection and discrimination abilities of the elderly, and give promise for differential diagnosis of speech understanding problems.Purpose The aim of the study was to compare the P1, N1, and P2 CAEP latencies and amplitudes in presbycusis with low and high word recognition score (WRS).Research Design A cross-sectional study design was used forthe study. Two groups were formed from the patients with presbycusis based on their scores on the speech recognition test.Study Sample Fifty-seven elderly volunteers participated in the study. The first group composed of 27 participants with high WRS, the other group composed of 30 participants with low WRS.Data Collection and Analysis The CAEP waves were recorded from these participants using speech signals. Latencies and amplitudes of P1 -N1-P2 waves of the two groups were compared with the f-test statistic.Results There were significant prolongation of P1 and N1 latencies in presbycusis with low WRS when compared with presbycusis with a relatively high word score (p < 0.05).Conclusion According to the result of the research, P1 and N1 latencies of presbycusis with low WRS were longer than the participants with high WRS. Factors affecting peripheral auditory system, such as stimulus sensation level, might be responsible for P1 and N1 latency prolongation of the low WRS group.
Keywords: audiology; auditory evoked potentials; geriatric; hearing loss; presbycusis